Second-trimester ultrasound and neuropathologic findings in congenital Zika virus infection (2018)
Zika virus is a mosquito-borne virus that causes congenital Zika syndrome, characterized by microcephaly and other fetal brain anomalies. This case report presents a case of Zika virus-related fetal brain anomalies including pathologic evidence of cerebral neuronal apoptosis and macrophage infiltrates and intracerebral calcification, ventriculomegaly and corpus callosum dysgenesis detected by ultrasound at 18 weeks of pregnancy.